Badr al-Jamālī and the Mosques of Aswan: New Considerations Based on a Building Inscription from the Museum für Islamische Kunst in Berlin - Schmidt, Stefanie (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
The article revisits the discourse on the impact of Badr al-Jamālī on the construction of minarets and mosques in Upper Egypt and substantiates this with regional evidence based on a building inscription of a mosque in Aswan. The inscription, currently housed in the Museum für Islamische Kunst in Berlin, dates from the year A.H. 491/1098 C.E. It is argued that the builder of the mosque, who can be identified as a high-ranking official in Upper Egypt, had affiliations with Badr al-Jamālī and his son through patronage. In addition, the paper publishes for the first time the brick band inscription on the so-called Ṭābiya minaret, a tower from the Fatimid era that was demolished in 2021 for unknown reasons without any historical building documentation. At the end of the article, the earliest datable mosque (318/930) and minaret are identified for Aswan.